Hyaluronic acid production by utilizing agro-industrial waste cane molasses - Shukla P.; Anand S.; Srivastava P.; Mishra A. (My University, 2025)
Hyaluronic acid is a polysaccharide endowed with distinctive biological and physiological competencies. Given its queer properties, hyaluronic acid has exclusive praxis in the cosmetics and medical industries. The surmounting demand for hyaluronic acid is the propulsion behind the necessity for finding the amenable ways for its production. Fermentation progression of Streptococcus zooepidemicus is reckoned as the superlative prompt and ambient approach for hyaluronic acid fabrication. For the unabated advancements in the industrial production of hyaluronan, industrial byproducts utilization is a fateful stile. The recent perusal is to optimize the fermentation production conditions of hyaluronic acid using cane molasses (a byproduct of sugar production) as a carbon source. The impact of different ranges of temperatures (33–41 °C), pH (6–8), and agitation rates (100–250 rpm) on the production process was calibrated using RSM using CCD as a statistical modality. In a 3.7 L bioreactor, 3.31 g/L hyaluronic acid was achieved at 9.74 percent molasses, 36.2 °C, pH 6.46, and a 207 rpm agitation rate using a batch fermentation technique. With a pH of 7, HPLC was conducted at 25 °C using a C18 column at a rate of 0.8 ml/min, and the wavelength was determined using a UV detector. The average retention time was 2.202 min. The FT-IR spectrum's output was also observed, and it matched the standard hyaluronic acid well. © 2022, King Abdulaziz City for Science and Technology.